Development and application of ultrasonic soldering for lap joint between glass and pewter (Sn5Sb1.2Cu) - Mohd Yusry Mustafa (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The research focused on the development and application of ultrasonic soldering for lap joints between flat soda lime glass and pewter (Sn5Sb1.2Cu). Pewter is a low melting temperature Sn based alloy. Ultrasonic soldering of the substrates was conducted using heat and ultrasonic vibrations pressure from 'Sunbonder USM-5' soldering machine. The objective was to strengthen soldering adhesion between the substrates measured through tensile test. New lead free low temperature solders were developed by alloying Sn40Bi with Al, Mg, Zn and Ag. (Sn40Bi)0.3Mg and (Sn40Bi)0.5Al solders with liquidus temperatures at 170.8ºC and 171.1ºC were selected for subsequent experiments. The liquidus temperatures were derived from phase diagrams attained by thermogravimetric analysis. Characterization of solder joints was conducted using scanning electron microscope and energy dispersive X-ray spectroscopy. Sn and Bi from both solders remained in metallic form without adhering to glass. Mg and Al passivated to metal oxides forming MgO and Al2O3 respectively. SiO2 from glass formed metal oxide bonds of Mg-O-Si with MgO and Al-O-Si with Al2O3. Mg-O-Si bond was stronger than Al-O-Si for glass surface with roughness below 0.15 µm. MgO with lower bond dissociation energy than Al2O3 at 358 kJ/mol formed bond with SiO2 by sharing electrons of oxygen atoms. (Sn40Bi)0.5Al bond to glass was stronger than (Sn40Bi)0.3Mg for rougher glass surface at above 0.15 µm. Al2O3 and MgO from the molten solders formed protrusions within the crevices in rougher glass surface. Al2O3 with greater fracture toughness of 4 MPa.m1/2 than MgO was more difficult to break during separation in tensile test. Bond between glass and solders consist of surface energy, metal oxide and mechanical adhesions. Optimizations on ultrasonic soldering parameters involved soldering temperature, ultrasonic power (vibration amplitude) and glass surface roughness. Shear separation strength and shear separation energy were derived from the tensile stress test during optimization. Adhesion strength and energy increased with increasing soldering temperature and glass surface roughness. Improvement through increasing solder temperature is due to lower viscosity and higher flow rate of molten solder. Soldering temperature maximum level is limited by the solidus temperature of Sn5Sb1.2Cu. At 460ºC, part of Sn5Sb1.2Cu melted off. Improvement through higher surface roughness is due to formation of numerous crevices on glass. Surface roughness maximum level was limited by weakening glass structure. Adhesion strength and energy peaked at vibration power of 8W. Increasing vibration amplitude formed stronger metal oxide bond and initiated deeper flow into crevices resulting in stronger mechanical adhesion. Very high vibration amplitude caused breakages of adjacent soldering bond. Study on the effect of temperature to adhesion strength was conducted through tensile test at 25ºC and 110ºC. Adhesion strength and energy decreased with increasing tensile test temperature. The softening solder from higher temperature weakened metal oxide and mechanical adhesions. Final work focused on validating shear separation forces formulations derived from the experimental results. Shear separation forces during glass fractures were compared with independently calculated force for fracturing glass. The formulations were validated by lower shear separation forces when compared to glass fracturing force.